2002
DOI: 10.1007/pl00007521
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after conservative laryngeal surgery: a multidimensional method of evaluation

Abstract: Assessment of quality of life (QoL) and satisfaction with care are particularly important in the field of oncology. The definition of QoL and the requirements for its measurement are still a matter of debate, but it is generally accepted that QoL is a multidimensional concept involving three different domains: physical, psychological and social. The aim of this study was to test a simple, inexpensive, multidimensional method of QoL measurement, based both on patients' perception of clinical outcome and the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…All other studies that included acoustic analysis of patients undergoing SCL, that we could identify, were performed without age-matched controls. 2,3,5,8,11 Most of the investigators reported that F0 decreased in patients with SCL, as we observed, 2,3,5,8 while some authors noted increased F0 values. 12 The values of shimmer and jitter in our study group were found to be increased, similar to the literature.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…All other studies that included acoustic analysis of patients undergoing SCL, that we could identify, were performed without age-matched controls. 2,3,5,8,11 Most of the investigators reported that F0 decreased in patients with SCL, as we observed, 2,3,5,8 while some authors noted increased F0 values. 12 The values of shimmer and jitter in our study group were found to be increased, similar to the literature.…”
Section: Discussionsupporting
confidence: 71%
“…The acoustic parameters used for evaluating voice are F0, intensity, jitter, percentage jitter, shimmer and signal-to-noise ratio. [3][4][5]11 For acoustic and perceptual analysis, the mid-portion (3 sec) of the sustained /a/ vowel was used, as this method was reported to be the most appropriate. 5 Perturbation measures (in period and amplitude) and harmonicsto-noise computations have emerged as the most robust measures.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In addition, SL enables preservation of the glottis with acceptable functional outcomes. 8,9 Vigili et al 11 compared SL to horizontal glottectomy and supracricoid laryngectomy and reported that SL had superior results in terms of quality of life. Although studies have examined vocal outcomes following SL, 12,13 none have determined outcomes based on the extent of resection.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 In addition, patients often suffer from insufficient airway and/or poor quality of speech. 3,6,9,10 This tendency is significantly worsened when PC is applied to HSE. 3,6,9 Rademaker et al reported that patients who underwent PC after HSE required the average of 121 days before starting oral intake, and half of these patients were not free from the feeding tube.…”
Section: Discussionmentioning
confidence: 99%